Is There a Paradigm Shift from Application of Caveat Emptor to Caveat Venditor in the Sale of Goods in Ghana? A Comparative Analysis of the Application of the Principle Caveat Emptor. - Edmund Nelson Amasah; Enoch Kwabena Amoah; Joseph Bondzie Afrifa (E-Journal of Humanities, Arts and Social Sciences, 2022)
This study seeks to analyse, compare and determine the extent to which various legal jurisdictions have prioritized the protection of buyers in sale of goods contracts. A doctrinal legal research approach was adopted in carrying out the study. The study found that at the end of the 19th century, most legal systems are gradually making statutory attempts as well as judicial pronouncements to prioritize the application of the principle of Caveat venditor over the principle of Caveat emptor. The study, therefore, calls for an amendment of the Sale of Goods Act, 1962 (Act 137) to codify judicial decisions made on these concepts into statutory provisions to meet the requirements of legal validity and the exigencies of time. This would go a long way to boost consumer protection and largely, the socio-economic interests of buyers in Ghana.